Pharmacognostic Evaluation of the Berries Containing Seeds of Vitis Vinifera Linn. (VITACEAE): A comprehensive study on the chemical and anatomical properties of Vitis vinifera berries and seeds (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The berries bearing seeds of Vitis vinifera form a prime source of polyphenol compounds. A preliminary phytochemical screening was done to reveal the presence of different phytochemicals like carbohydrates, flavonoids, glycosides, tannins, sterols and fixed oils. The macroscopic and microscopic characters of its seeds was also studied.